EBV‐Positive and EBV‐Negative Posttransplant Diffuse Large B Cell Lymphomas Have Distinct Genomic and Transcriptomic Features. (18th January 2016) - Finalet Ferreiro, J.; Morscio, J.; Dierickx, D.; Vandenberghe, P.; Gheysens, O.; Verhoef, G.; Zamani, M.; Tousseyn, T.; Wlodarska, I.
Abstract : The molecular pathogenesis of posttransplant diffuse large B cell lymphoma (PT‐DLBCL) is largely unknown. We have recently shown that Epstein‐Barr virus–positive (EBV + ) and –negative (EBV − ) PT‐DLBCL have distinct gene expression profiles, and the transcriptomic profile of EBV − PT‐DLBCL is similar to that of DLBCL in immunocompetent individuals (IC‐DLBCL). To validate these observations at the genomic level, we performed array–comparative genome hybridization (aCGH) analysis of 21 EBV + PT‐DLBCL, 6 EBV − PT‐DLBCL, and 11 control IC‐DLBCL, and subsequently combined genomic and transcriptomic data. The analysis showed that EBV + and EBV − PT‐DLBCL have distinct aCGH profiles and shared only one recurrent imbalance. EBV − PT‐DLBCL, however, displayed at least 10 aberrations recurrent in IC‐DLBCL, among which characteristic gain of 3/3q and 18q, and loss of 6q23/ TNFAIP3 as well as 9p21/ CDKN2A . The most prevalent aberration in EBV + PT‐DLBCL was gain/amplification of 9p24.1 targeting PDCD1LG2/PDL2 . Our data indicate that the FOXP1 oncogene and the tumor suppressor CDKNA2 implicated in EBV − DLBCL, do not play a critical role in the pathogenesis of EBV + PT‐DLBCL. Altogether, genomic profiling of PT‐/IC‐DLBCL confirms that EBV − and EBV + PT‐DLBCL are distinct entities, while EBV − PT‐DLBCL has features in common with IC‐DLBCL. These findings support the hypothesis that EBV − PT‐DLBCL are de novo lymphomas in transplant recipients.